WORKSHOPS: POLICIES AND STRATEGIES FOR SUPPORTING THE TALENTED YOUTH IN TECHNICAL FIELD - ANGHEL IONICA-ONA (Studia Universitatis Babes-Bolyai, 2014)
ABSTRACT. Supporting talented youth is an important condition for both the professional development of this special population and the economic development of the host country. This paper aims to explore the scholars' and students' opinions on the involvement of various institutions in supporting talented youth in technical by implementing different educational policies and strategies. On this purpose we organized two workshops involving professors and PhD Students from the Technical University of Iași, Romania. The collected data were processed according the requirements of the qualitative analyzes. The results show a general distrust of the participants in state institutions or non-governmental organizations, while the university is to be seen as the one supporting the youth showing a talent in the technical.